Visceral pentastomiasis caused by Armillifer armillatus in a captive striped hyena (Hyaena hyaena) in Chiang Mai Night Safari, Thailand - Dechkajorn S. (2017)
© 2015 Elsevier Ireland Ltd. Visceral pentastomiasis (porocephalosis) caused by Armillifer armillatus larvae was incidentally diagnosed in a female striped hyena (Hyaena hyaena) of unknown age which died unexpectedly in 2013. The hyena had been imported from Tanzania 8. years earlier and have been since then in a zoo in Chiang Mai, northern Thailand. Pathological examination revealed visceral nymph migrans of pentastomes throughout the intestine, liver, diaphragm, omentum and mesentery, spleen, kidneys, and urinary bladder. Polymerase chain reaction and sequencing that targeted the pentastomid-specific 18S rRNA gene determined 100% identity with reference sequence for A. armillatus, suggesting that its ova can infect the hyena to serve as an intermediate host for the parasite. Further studies to identify the source of infection, its risk factors, and host range for A. armillatus are important to determine its zoonotic potential and to better prevent and manage the disease to protect animal and human health.